The Need to Define the Substantive Jurisdiction of Administrative Courts Through a General Clause - Szafrańska, Weronika (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The aim of the paper is to assess whether the amendment to Art. 3 of the Law on Proceedings Before Administrative Courts proposed in legal community, which consists in determining the material jurisdiction of administrative courts using the general clause method, is a good solution. The considerations were preceded by a short observation on the linguistic inaccuracies occuring in the discussed issues. Then, the historical process of shaping the two main methods of further specifying the material jurisdiction of courts is presented: general clause and enumeration. As the proposed changes to Polish regulations are based on solutions adopted in German administrative court proceedings, the article addresses the problems faced by judges of German administrative courts when applying the general clause. Its interpretation causes many problems and providing an insight into them may be a valuable source of information for the Polish legislator.